Penerapan Pelayanan Prima (Service Excellent) pada Pemeriksaan X-Ray di Bandar Udara Internasional Adi Soemarmo Solo - Achmad Bagas Surya; Andi Syaputra (MES Bogor, 2024)
Excellent service has an important role in a business in the field of aviation companies. The main factor in providing satisfaction for customers is that excellent service can provide satisfaction to customers which will then certainly provide good value to the sustainability of the company. Airports have facilities and infrastructure to support service activities such as implementing excellent service at X-Ray checks. Aviation Security officers must apply good excellent service to generate trust and satisfaction to passengers so that researchers are interested in knowing how the application of excellent service by Aviation Security officers to passengers when checking luggage on X-Ray machines and what should be developed in excellent service to passengers at Adi Soemarmo Solo International Airport. This research uses qualitative methods, namely data collection methods in the form of interviews, observation, and documentation. The data obtained in the form of interviews with Aviation Security officers at Adi Soemarmo Solo International Airport and documents used to carry out daily activities. The results of this study indicate an explanation of the data taken by researchers both in terms of observation, interviews, and documentation that the form of service at the X-Ray inspection is the passenger luggage organizer, X-Ray operator, and manual checking of luggage. The results of researcher observations in the application of excellent service to passengers are only 50% and prioritize flight safety security 50%. Based on data sources from interviews conducted by researchers, that the implementation of excellent service strategies carried out by Aviation Security officers is by Applying Hospitality, Organizing passenger queues, Maximizing personnel, and the 3S + 1C Concept.